Bmi1 signaling maintains the plasticity of airway epithelial progenitors in response to persistent silica exposures. (30th March 2022) - Yang, Jiali; Wu, Shuang; Hu, Wenfeng; Yang, Dandan; Ma, Jia; Cai, Qian; Xue, Jing; Chen, Juan; Li, Feng; Zeng, Jing; Liu, Xiaoming
Abstract: Silicosis is caused by the continuous inhalation of environmental silica dust. The repetitive exposure of silica induces airway epithelial cell injury, leads proliferative exhaustion of epithelial stem cells, ultimately results in the lung remodeling and the development of silicosis. The B-cell-specific Moloney murine leukemia virus integration site 1 (Bmi1) is a pivotal transcription factor in stem cell self-renewal and proliferation of many tissues including the lung, but its role in the airway basal cell proliferation and differentiation during the pathogenesis of silicosis in lung has yet been investigated. In this study, the function of Bmi1 in airway basal cell proliferation and differentiation in response to silica challenge was investigated in lungs of silicosis mice and primary human bronchial epithelia cells (HBECs) exposed to silica dioxide (SiO2 ). Results showed a decreased expression of Bmi1 protein, epithelial basal cell markers Krt14 and Krt5, club cell marker Clara cell secretory protein, and ciliated cell marker acetyl-α-tubulin in silicosis lungs, compared to healthy mice. In consistence, a persistent exposure of SiO2 reduced the capacity of cell proliferation and differentiation in HBECs, as ascertained by the reduction of differentiated epithelial cell markers and BMI1 expression, while an increased P21-positive senescent cell fraction. Moreover, an overexpression of BMI1 in HBECs reduced the SiO2 -senescent cells, enhanced the potency of cell proliferation and differentiation, and increased capacity of airway epithelial regeneration in response to the persistent exposure of SiO2 . These data suggest that Bmi1 is a key transcription factor engaging in maintaining the self-renewal, proliferation and differentiation of epithelial stem cells in lung during the development of silicosis disease.